“A Private Woe” - Laboni Mukherjee (Sanglap: Journal of Literary and Cultural Inquiry)
This paper tries to find out an adequately race-sensitive definition of the everyday. It contrasts universalized ideas of the everyday as underlined by Rita Felski with specific instances of racist violence described in Audre Lorde’s biomythography Zami: A New Spelling of my Name. It illustrates Felski’s inadequacy in describing the everyday from the perspective of black experience of racist violence. It posits racist violence as a paradoxical phenomenon – it is mundane and everyday while disrupting the everyday. It then questions Andrew Smith’s assertion that the ‘black everyday’ is structurally impossible. The paper also challenges the position of the black individual in a binary of being triumphant or tragic, instead of being ordinary. Taking inspiration from scholars like Matthew F. Delmont, Saidiya Hartman and Christina Sharpe, this paper presents an alternative definition of the everyday, highlighting black people’s ability to recalibrate their everyday narratives despite racist violence, while also presenting definitions of ‘blackness’ beyond skin colour and violence and including the beautiful aspects of their cultural traditions. This paper then problematizes Felski’s assertion that the everyday is “secular” by engaging with the text and the biomythography as a genre.